Choosing one at a time? Presenting options simultaneously helps people make more optimal decisions than presenting options sequentially - Basu, Shankha (2017)
This research examines an element of choice architecture that has received little attention—whether options are presented simultaneously or sequentially. Participants were more likely to choose dominating options when the options were presented simultaneously rather than sequentially, both when the dominance relationship was transparent (Experiment 1) and when it was not (Experiments 2–3). Depth of cognitive processing mediated the effect of option presentation on optimal choice (Experiment 4). Memory load was unlikely to be the underlying mechanism, as individual differences in working memory span did not predict optimal choice in the sequential condition (which places a greater memory load; Experiment 5), and manipulations of memory load did not reduce the benefits of simultaneous presentation (Experiments 6a–6c). Instead, participants’ working memory span predicted optimal choice in the simultaneous condition (which allows for more in-depth processing; Experiment 5), and a manipulation of processing load eliminated the benefits of simultaneous presentation (Experiment 7).